Pengaruh Citra Merek dan Fasilitas dalam Meningkatkan Kualitas Pelayanan serta Implikasinya terhadap Kepuasan Pasien di UPTD Puskesmas Kertajati, Kabupaten Majalengka - Aprillia, Meirza; Yuliati, Farida; Wirawan, Chevi; Paramarta, Vip; Rulia, Rulia (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Patient satisfaction is the main indicator of service quality and performance in Puskesmas. In UPTD Puskesmas Kertajati, low patient satisfaction has an impact on accreditation which only reaches the main level. Factors that influence patient satisfaction include brand image, service quality, and facilities. This study analyzes the effect of brand image and facilities on patient satisfaction through service quality. Using a descriptive verification method, this study examines brand image and facilities as exogenous variables, service quality as an intervening variable, and patient satisfaction as an endogenous variable. The research sample consisted of 303 patients selected through purposive sampling techniques. This study uses quantitative data collected through questionnaires and analyzed using Path Analysis. The results showed that brand image, facilities, service quality, and patient satisfaction were in the "very good" category. Brand image and facilities significantly influence service quality, which ultimately has a strong positive impact on patient satisfaction. Service quality acts as a perfect mediating variable in the relationship between brand image and patient satisfaction, indicating a strong correlation between the two. To improve patient satisfaction, UPTD Puskesmas Kertajati needs to improve its reputation by training human resources, optimizing the layout of the waiting room, and fostering empathy among medical personnel. A culture of continuous improvement is essential to improving service quality and maintaining competitiveness with other health service centers.